Onion (Allium cepa L.) peel extract effects on 3T3-L1 adipocytes and high-fat diet-induced obese mice. (June 2021) - Yu, Shuai; Li, Hongmei; Cui, Taihua; Cui, Mingxun; Piao, Chunxiang; Wang, Shitong; Ju, Ming; Liu, Xin; Zhou, Guanghong; Xu, Hongyan; Li, Guanhao
Abstract: Obesity is a serious medical condition and can lead to multiple health problems. Commercial diet pills are available, however, they have several side effects. It is therefore important to develop anti-obesity supplements without negatively affecting health. Onions are consumed in daily life, wasted onion peel may be useful to improve obesity management as a safer material because of their flavonoids. 3T3-L1 Pre-adipocytes as well as C57BL/6J mice on a high-fat diet (HFD) were used to test the anti-obesity effects of onion peel extract (OPE) in vitro and in vivo . OPE significantly decreased the lipids of 3T3-L1 cells and inhibited lipid accumulation by reducing the expression of lipogenesis-related genes such as peroxisome proliferator-activated receptor-γ, CCAAT/enhancer binding protein, fatty acid synthase, and acetyl CoA carboxylase. Compared to mice on the HFD, OPE-treated mice weighed significantly less. OPE-treated mice had a lower fat coefficient, and serum concentrations of triglyceride, total cholesterol, and low density lipoprotein cholesterol compared to the mice on the HFD. The expression levels of adipogenesis genes were significantly decreased after OPE treatment. The results showed that OPE inhibited lipid accumulation by down regulating adipogenesis gene expression and reduced the hypertrophy of adipose tissue. These results suggested that OPE has potential anti-obesity effects, and may provide a potential material for the development of natural anti-obesity foods and nutritional supplements based on OPE.